An experiment on software test creation: can EvoSuite help test teaching? - Santos, Lucas; Sousa, Neto; Gomes, Laís; Garcia, Jannielly; Ferreira, Fischer (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2023: Anais do XXII Simpósio Brasileiro de Qualidade de Software, 2023)
This paper presents the execution of a software testing experiment, where participants were tasked with identifying test cases from a provided software system and implementing the identified test cases. The objective of this study was to investigate students’ perception in test case creation. Participants were divided into two groups: a control group, which received the source code and documentation, and an experimental group, which received, in addition to the source code and documentation, a test suite generated by the EvoSuite tool. Furthermore, participants responded to three questionnaires: one about the project, another about their prior knowledge profile, and one providing feedback on their perception of the experiment and software testing education. Participants made it clear that the EvoSuite tool helped uncover new test scenarios. Additionally, it assisted in identifying new ways to test code segments that participants previously had no prior knowledge of how to access. Overall, the study suggests that the use of code generation tools can be a valuable addition to software testing education, aiding students in developing their testing skills and improving the quality of their tests. This work can benefit both teachers and students in computer science-related courses.